المحافظات غير المنتظمة في إقليم بين المركزية واللامركزية الإدارية - كاظم حسن الربيعي (Journal of Madenat Alelem University College, 2011)
By highlighting the legal governorates old and new shows that botn aaopteddecentralized management, whether in law or in the Constitution, for the Act | No.159 of 1969, which ran until 2008 according to the reasons for it been necessarylegislation law, the Department supports the principles of administrativedecentralization to achieve the aspirations and expectations of its citizens, for thisnominated boards through democratic elections, state-sponsored at the time, andsupervised by the Minister of the Interior is empowered by these councils in allprovinces clear and definite authority to walk affairs and even more of them nowhave an independent budget and fixed income, but that these powers did not lastlong but affected by political circumstances and social conditions prevailing thenexported Legislative Reform Act No. 35 of 1977, which said (that every societywhere there are one authority, one for each state its political one and that meansthere is the idea of the multiplicity of the legislative, executive and judicialbranches of this has become necessary to reconsider the law of the provinces toremain a representative of the central authority in the country) this is disabled theprovincial councils election and to put the appointment on the side of the electionon the boards of the provinces and limited membership in the provincial councilsof these appointees only, without elected not to mention the disruption of many ofthe powers and functions granted to the boards of the provinces and limit thevalidity of all However, the central authority from the Minister to the Governor, tothe greatest staff in the far marshes and villages and districts in addition to theregulations and instructions that determine the freedom of the central persons inthe ownership, mobility and travel, journalism and publishing and other.In the Constitution of the Republic of Iraq for the year 2005 is the time, which wentfirst to the establishment of territories within six months from the date of issuanceby request of one third of the members of the provincial council or a tenth of thevoters in each province returned issued a Law of Governorates not organized intoa Region No. 21 of 2008 for the purpose of organizing jurisdiction and powers inline with the shape of the new state-based federal system, federal anddecentralized system as stated in the reasons for this law is not the whole truth,but because of faltering experience in the Kurdistan region and its readiness forindependence from Iraq with the knowledge of an independent and anindependent budget, army and police special tags and the limits of the disputedAs stated in Article 140 of the Constitution do not know how it is permissible forlawmakers mention of the disputed border and tame them with the Iraqis theyterm a border with neighboring countries and not the boundary between theprovinces of Iraq, which is subject to the Central Authority identified only .